(untitled) (Historia, 2021)
The post-emancipation Cape presents a picture of a poor, pre-industrial colony, in which agriculture was the predominant economic activity. The division of society into propertied and unpropertied classes corresponded substantially with its division racially into white and black, Whites, as the Rev, Boyce noted at the end of the post-emancipation apprenticeship period, were "the capitalists of the country, and with some few exceptions, the sole proprietors of the soil". Conversely, coloureds were primarily wage earners, whose previous condition of servitude had precluded them from "the opportunity of accumulating any capital", and in whom habits of "independent resources and energy" needed to be created.